Electronic copyright and the law librarian. - OPPENHEIM, Charles (1994)
Discusses copyright issues of relevance to electronic databases and their uses, and software and electrocopying. Explains that output from online databases is controlled by the contract with the host operator, and the contractual terms take precedent over any copyright law terms.